Determining Whether Agonist Density or Agonist Number Is More Important for Immune Activation via Micoparticle Based Assay - Deak, Peter; Kimani, Flora; Cassaidy, Brittney; Esser-Kahn, Aaron (Frontiers in Immunology, 2020)
It is unknown if surface bound toll-like-receptor (TLR) agonists activate cells via density or total molecular number. To answer this question, we developed a TLR agonist surface conjugated polystyrene microparticle (MP) system. Using a library of MPs with varying TLR agonist density and number, we simultaneously observed innate immune cell MP uptake and TNFα expression using ImageStream flow cytometry on a cell by cell basis. The data shows that total TLR number and not density drives cellular activation with a threshold of approximately 105–106 TLR agonists. We believe that this information will be crucial for the design of particulate vaccine formulations.